Risk Factors for Disease Occurrence in Pig farming in Medan Belawan sub-district, Medan City - Laurensia V D Manurung; Ahmad Sadeli; R Edhy Mirwandhono (Talenta Publisher, 2024)
Pigs are one of the commodities that have been reported with many cases of sudden death due to outbreaks of disease viruses, so it is necessary to identify risk factors that have the potential to play a role in the emergence/transmission of disease viruses in pigs in Medan Belawan District. This study aims to identify several risk factors that have the potential to be sources of disease transmission, includes pen management, biosecurity management, waste management, disease prevention systems, sanitation and disinfection, carcass disposal systems and how these factors influence disease emergence in pig farming businesses. This research is a quantitative design that uses non-probability sampling with purposive sampling technique. The number of samples were 70 farmers from 3 sub-districts in Medan Belawan District, namely: Bagan Deli Village, Belawan Bahagia Village and Belawan Sicanang Village. The instrument test used is the validity and reliability test. The results of this study are that pen management partially has a positive effect on the risk of disease emergence in pig farming businesses, with a t-value of 2.258 and a sig. value of 0.028, Biosecurity management partially has a positive effect, with a t-value of 7.526 and a sig. value <,001, Waste processing partially has a positive effect, with a t-value of 2.390 and a sig. value. 0.017, partial disease prevention has a positive effect, with a t-value of 2.453 and a sig. value of 0.031, partial sanitation and disinfection have a positive effect, with a t-value of 5.047 and a sig. value <0.001, the carcass disposal system partially does not have a significant effect on the risk of disease emergence in pig farming, with a t-value of -0.733 and a sig. value of 0.466. The conclusion of this study that the independent variables/ risk factors as a whole have a significant effect on the dependent variable/ disease emergence